Fast and slow precipitation responses to individual climate forcers: A PDRMIP multimodel study. Issue 6 (16th March 2016) - Samset, B. H.; Myhre, G.; Forster, P. M.; Hodnebrog, Ø.; Andrews, T.; Faluvegi, G.; Fläschner, D.; Kasoar, M.; Kharin, V.; Kirkevåg, A.; Lamarque, J.‐F.; Olivié, D.; et al.
Abstract: Precipitation is expected to respond differently to various drivers of anthropogenic climate change. We present the first results from the Precipitation Driver and Response Model Intercomparison Project (PDRMIP), where nine global climate models have perturbed CO2, CH4, black carbon, sulfate, and solar insolation. We divide the resulting changes to global mean and regional precipitation into fast responses that scale with changes in atmospheric absorption and slow responses scaling with surface temperature change. While the overall features are broadly similar between models, we find significant regional intermodel variability, especially over land. Black carbon stands out as a component that may cause significant model diversity in predicted precipitation change. Processes linked to atmospheric absorption are less consistently modeled than those linked to top‐of‐atmosphere radiative forcing. We identify a number of land regions where the model ensemble consistently predicts that fast precipitation responses to climate perturbations dominate over the slow, temperature‐driven responses. Key Points: Precipitation response from five climate drivers shown for nine climate models Fast responses scale with atmospheric absorption, slow with surface temperature Over some land regions, fast precipitation responses dominate the slow response